2017
DOI: 10.1097/md.0000000000006440
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of palatal rugae pattern in different sagittal skeletal relationship adolescent subjects

Abstract: The purpose of this study was to evaluate the morphological structure of palatal rugae in Turkish orthodontic subjects with different sagittal skeletal malocclusions. Orthodontic dental casts of 105 patients (Class I [23 females, 12 males]; 35, Class II [18 females, 17 males]; and 35, Class III [14 females, 21 males] 10–22 years old) were analyzed for rugae patterns. Palatal rugae pattern and number, direction of rugae alignment, shape of incisive papilla were analyzed. Modified Thomas and Kotze classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…A study done by Oral et al, reported that wavy type of rugae was the most common pattern in different sagittal skeletal malocclusion groups of Turkish background, 17 which was consistent with the present study. Class II skeletal malocclusion group showed a significant difference for the mean number of rugae on right and left sides of the mid-palatine raphae but no significant difference was noted among the three groups, which is consistent with those reported by Suhartono et al 18 and Oral et al 17…”
Section: Discussionsupporting
confidence: 93%
“…A study done by Oral et al, reported that wavy type of rugae was the most common pattern in different sagittal skeletal malocclusion groups of Turkish background, 17 which was consistent with the present study. Class II skeletal malocclusion group showed a significant difference for the mean number of rugae on right and left sides of the mid-palatine raphae but no significant difference was noted among the three groups, which is consistent with those reported by Suhartono et al 18 and Oral et al 17…”
Section: Discussionsupporting
confidence: 93%
“…Se puede complicar la identificación humana si se basa en la rugoscopía de un paciente con antecedente de ortodoncia, tomado en cuenta para comparar el registro palatal actual con el preortodóntico [52][53]. Por lo tanto, es indispensable, al finalizar el tratamiento, obtener un nuevo registro palatal, ya sea en yeso o en Vacu Press con o sin chip [54].…”
Section: La Rugoscopía En Contextos Específicosunclassified
“…1 The Palatal Rugae vary in height, shape, width, number, and location from person to person, when compared the both sides of hard palate, demonstrating individuality. 8 This design illustrates non-specific and specific characteristics but moreover within-species individuality; among the people, On each side of the midline, there are between 2 and 7 rugae with varying morphologies. 9 The palatal rugae start developing in 3rd month of embryonic life, 10 the appearance of PR does not change after this period, but the length of rugae pattern increases which shows normal growth pattern.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 However, only a few studies have been done in the past to determine the link of rugae pattern with various skeletal and dental mal-occlusions. 34,46,47,48 Oral et al reported wavy and curved rugae pattern with different skeletal and dental mal-occlusions 8 . Fatima n Fida in their study reported no particular pattern was related with different sagittal skeletal pattern 34 .…”
Section: Introductionmentioning
confidence: 99%